1999
DOI: 10.1017/s1355617799533031
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral deficits in Persian Gulf veterans: Evidence from a population-based study

Abstract: Reports of low-concentration nerve gas exposures during the Persian Gulf War have spurred concern about possible health consequences and refocused interest on the symptoms reported by many returning military veterans. The Portland Environmental Hazards Research Center is studying veterans from the Northwest USA who report persistent, unexplained " Persian Gulf" symptoms (cases) or who do not report those symptoms (controls). Of the first 101 veterans studied, cases differed substantially from controls on a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…The inhibition difficulty noted here in the subjects' performance was accompanied by ERPs whose NOGO P3 was significantly reduced in amplitude, whereas the NOGO N2 amplitudes were neither significantly different from those of the control group nor different from the GO N2 amplitudes. This is consistent with previous studies in other patient populations that have found compromised inhibitory response performance to be marked by blunted or absent NOGO P3 in the N2-P3 complex [44,45,[53][54][55].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The inhibition difficulty noted here in the subjects' performance was accompanied by ERPs whose NOGO P3 was significantly reduced in amplitude, whereas the NOGO N2 amplitudes were neither significantly different from those of the control group nor different from the GO N2 amplitudes. This is consistent with previous studies in other patient populations that have found compromised inhibitory response performance to be marked by blunted or absent NOGO P3 in the N2-P3 complex [44,45,[53][54][55].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have found performance decrements in the Wisconsin Cart Sort [8], Continuous Performance Test [8,43,54], Stroop tasks [10,14,15], sustained attention [7], and Digit Span tasks [8,10,15,55], all of which are considered markers of frontal lobe dysfunction. These findings are supported by neuroimaging results suggesting decreased perfusion in the superior-and midfrontal regions bilaterally in ill GW veterans [56].…”
Section: Discussionmentioning
confidence: 99%
“…The initial ®nding of the present report supports results of a recent population-based study, identifying a subgroup of Gulf veterans with`P G[Persian Gulf] symptoms'' as``slow cases'' (Anger et al, 1999). Gulf Veterans in that study had to ful®l inclusion criteria similar to those employed in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Compared to``other cases'', the subgroup of``slow cases'' had signi®cant problems on measures involving working memory and attention. In their report, Anger et al (1999) suggested that the de®cits observed in this slow responding group of symptomatic Gulf veterans could be associated with either environmental (neurotoxic) exposure or psychological distress incurred as a consequence of participating in the Gulf War.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation